Transcriptional Profiling of ESTs from the Biocontrol Fungus Chaetomium cupreum - Haiyan Zhang; Min Li (The Scientific World Journal)
Comparative analysis was applied to two cDNA/ESTs libraries (C1 and C2) from Chaetomium cupreum. A total of 5538 ESTs were sequenced and assembled into 2162 unigenes including 585 contigs and 1577 singletons. BlastX analysis enabled the identification of 1211 unigenes with similarities to sequences in the public databases. MFS monosaccharide transporter was found as the gene expressed at the highest level in library C2, but no expression in C1. The majority of unigenes were library specific. Comparative analysis of the ESTs further revealed the difference of C. cupreum in gene expression and metabolic pathways between libraries. Two different sequences similar to the 48-KDa endochitinase and 46-KDa endochitinase were identified in libraries C1 and C2, respectively.